ANALISIS HUBUNGAN KESULITAN BELAJAR DENGAN PENGETAHUAN AWAL (PRIOR KNOWLEDGE) SISWA MENGGUNAKAN TES DIAGNOSTIK TWO-TIER PADA MATERI LARUTAN PENYANGGA DI SMAN 2 SOLOK - Handayani, Putri (journal of residu, 2019)
Buffer solutions are learning that many have early knowledge related to new lessons to be learned. Students can understand learning buffer solutions if the prior knowledge related to this material is understood. This study aims to analyze the relationship of prior knowledge with learning difficulties students in learning buffer solutions at SMAN 2 Solok. This type of research is Descriptive research on class XI students of SMAN 2 Solok by giving a test Two-Tier diagnostics. The research subjects were 34 students. Data analysis techniques are carried outquantitative aims to determine the percentage of student learning difficulties in learning buffer solution and percentage of learning difficulties in prior knowledge. From the research it was found that the percentage of students experiencing learning difficulties with a very high category average was not in accordance with scientific understanding, namely in the subject matter of the properties of buffer solution, capacity buffer solution, buffer solution mechanism, and pH of the buffer solution. Preliminary knowledge which affects the Bronsted Lowry ionization reaction, acid-base strength, acid base stoichiometry, acid-base pH and equilibrium constant. Keywords: Buffer solutions, Prior knowlede, Diagnostics test, Two-Tier